Systems approach to health service design, delivery and improvement: a systematic review and meta-analysis. Issue 1 (19th January 2021) - Komashie, Alexander; Ward, James; Bashford, Tom; Dickerson, Terry; Kaya, Gulsum Kubra; Liu, Yuanyuan; Kuhn, Isla; Günay, Aslι; Kohler, Katharina; Boddy, Nicholas; O'Kelly, Eugenia; Masters, Joseph; et al.
Abstract : Objectives: To systematically review the evidence base for a systems approach to healthcare design, delivery or improvement. Design: Systematic review with meta-analyses. Methods: Included were studies in any patients, in any healthcare setting where a systems approach was compared with usual care which reported quantitative results for any outcomes for both groups. We searched Medline, Embase, HMIC, Health Business Elite, Web of Science, Scopus, PsycINFO and CINAHL from inception to 28 May 2019 for relevant studies. These were screened, and data extracted independently and in duplicate. Study outcomes were stratified by study design and whether they reported patient and/or service outcomes. Meta-analysis was conducted with Revman software V.5.3 using ORs—heterogeneity was assessed using I 2 statistics. Results: Of 11 405 records 35 studies were included, of which 28 (80%) were before-and-after design only, five were both before-and-after and concurrent design, and two were randomised controlled trials (RCTs). There was heterogeneity of interventions and wide variation in reported outcome types. Almost all results showed health improvement where systems approaches were used. Study quality varied widely. Exploratory meta-analysis of these suggested favourable effects on both patient outcomes (n=14, OR=0.52 (95% CI 0.38 to 0.71) I 2 =91%), and service outcomes (n=18, OR=0.40 (95% CI 0.31 to 0.52) I 2 =97%). Conclusions: This study suggests that a systems approaches to healthcare design and delivery results in a statistically significant improvement to both patient and service outcomes. However, better quality studies, particularly RCTs are needed. PROSPERO registration number CRD42017065920.